Lactic acid fermentation of shrimp waste - Lekamwasam L.S.S.K. De Silva (1989)
The enzymic hydrolysis of shrimp waste, stabilises using an acid fermentation technique, was observed to develop a mechanism to separate and isolate useful products, such as proteins, chitin and astaxanthin. Initially the effectiveness of the fermentation technique was studied with added carbohydrate (lactose) with an innoculum (Stabisil, comprising of Streptococcus faecium strains M74, Lactobacillus plantarum and Pediococus acidilacti). [Continues.]